Natural Compounds with Proteasome Inhibitory Activity for Cancer Prevention and Treatment - Yang, H.; Landis-Piwowar, K. R.; Chen, D.; Milacic, V.; Dou, Q. P. (Current Protein and Peptide Science, 2008)
The proteasome is a multicatalytic protease complex that degrades most endogenous proteins including misfolded or damaged proteins to ensure normal cellular function. The ubiquitin-proteasome degradation pathway plays an essential role in multiple cellular processes, including cell cycle progression, proliferation, apoptosis and angiogenesis. It has been shown that human cancer cells are more sensitive to proteasome inhibition than normal cells, indicating that a proteasome inhibitor could be used as a novel anticancer drug. Indeed, this idea has been supported by the encouraging results of the clinical trials using the proteasome inhibitor Bortezomib (Velcade, PS-341), a drug approved by the US Food and Drug Administration (FDA). Several natural compounds, including the microbial metabolite lactacystin, green tea polyphenols, and traditional medicinal triterpenes, have been shown to be potent proteasome inhibitors. These findings suggest the potential use of natural proteasome inhibitors as not only chemopreventive and chemotherapeutic agents, but also tumor sensitizers to conventional radiotherapy and chemotherapy. In this review, we will summarize the structures and biological activities of the proteasome and several natural compounds with proteasome inhibitory activity, and will discuss the potential use of these compounds for the prevention and treatment of human cancers.
Keywords: cancer prevention